Transient Receptor Potential Channel 1 Potentially Serves as a Biomarker Indicating T/TNM Stages and Predicting Long-Term Prognosis in Patients With Renal Cell Carcinoma - Chen, Liang; Shan, Guang; Ge, Minghuan; Qian, Huijun; Xia, Yue (Frontiers in Surgery, 2022)
Background: Transient receptor potential channel 1 (TRPC1) regulates the progression of several cancers, but its clinical implication in renal cell carcinoma (RCC) hasn’t been explored yet. This study aimed to investigate the correlation of TRPC1 with clinical characteristics and prognosis in RCC patients. Methods: Totally, 177 primary RCC patients who received surgical resection were retrospectively screened. Their tumor and paired adjacent tissue specimens were retrieved to assess TRPC1 mRNA expression using reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and TRPC1 protein expression using immunohistochemistry (IHC). Results: Both TRPC1 IHC score and TRPC1 mRNA expression were elevated in RCC tissue than in adjacent tissue (both P<0.001); meanwhile, both TRPC1 IHC score and TRPC1 mRNA expression in tumor were associated with higher T stage (both P=0.020) and TNM stage (P=0.009, P=0.003, respectively). However, no correlation was found in tumor TRPC1 IHC score or TRPC1 mRNA expression with other tumor properties (all P>0.05). Besides, the 3-year, 5-year, and 7-year overall survival (OS) were: 81.4%, 68.6%, and 60.2%, respectively in patients with tumor TRPC1 protein high; then 89.3%, 82.7%, and 76.7%, respectively in patients with tumor TRPC1 protein low. TRPC1 protein high (vs. low) in tumor was associated with shorter OS (P=0.017), while TRPC1 mRNA high (vs. low) in tumor wasn’t correlated with OS (P=0.144). By the forward stepwise method, TRPC1 protein expression independently predicted poor OS (P=0.010, hazard ratio=2.052). Conclusion: TRPC1 serves as a potential biomarker reflecting tumor features and long-term survival profile in RCC patients.